PENINGKATAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI DENGAN MENGGUNAKAN PETA KONSEP BAGI SISWA KELAS IV SD NEGERI 02 LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Rummin Rummin (JRTI (Jurnal Riset Tindakan Indonesia), 2016)
Ability in writing essay is one of the vital aspects in learning Bahasa. The research is aimed to describe the gaining of ability in writing descriptive essay by using concept of mapping along pre, on going, and post of writing. Subject of research is grade IV at SDN 02 Lubuk Alung Padang Pariaman. The research was held in three cycles. Data of the research were obtained through observation sheets distributed to observer and students and assessment of students’ works (including concepts of mapping, blueprint of essay, and wholly essay). Data were analyzed by using qualitative analyzing. The researcher decide the standard of students’ achievement percentage as 80%. After the cycle I, got the students’ achievement percentage as 68,18%. After the cycle II, got an increasing of students' achievement perentage as 77,27%. Standard of students’ achievement percentage was achieved after the cycle III, that was 86,36%. The result of research show that the using of concepts of mapping can improve the students’ ability in writing descriptive essay.